Molecular Epidemiology and Risk Factors of Ventilator-Associated Pneumonia Infection Caused by Carbapenem-Resistant Enterobacteriaceae - Gao, Bo; Li, Xiandong; Yang, Fengmei; Chen, Wei; Zhao, Ying; Bai, Gang; Zhang, Zhaoyong (Frontiers in Pharmacology, 2019)
Ventilator-associated pneumonia (VAP) infection caused by carbapenem-resistant Enterobacteriaceae (CRE) is becoming more prevalent, thus seriously affecting patient outcomes. In this paper, we studied the drug resistance mechanism and epidemiological characteristics of CRE, and analyzed the infection and prognosis factors of VAP caused by CRE, to provide evidence for effective control of nosocomial infection in patients with VAP. A total of 58 non-repetitive CRE strains of VAP were collected from January 2016 to June 2018. To explore the risk factors of CRE infection, 1:2 group case control method was used to select non CRE infection patients at the same period as the control group. Among the 58 CRE strains, the most common isolates included Klebsiella pneumoniae and Escherichia coli. All strains were sensitive to polymyxin B, which features better sensitivity to other antibiotics such as minocycline, trimethoprim/sulfamethoxazole and amikacin. Multiple drug resistance genes were detected at the same time in most strains. KPC-2 was the most common carbapenemase-resistant gene in Klebsiella pneumoniae, whereas NDM-1 was more common in Escherichia coli. The risk factors correlated with CRE infection included intensive care unit (ICU) occupancy time >7 days (OR=2.793; 95% CI 1.439～5.421), antibiotic exposure during hospital stay including those to enzyme inhibitors (OR=1.977; 95% CI 1.025～3.812), carbapenems (OR=3.268; 95% CI 1.671～6.392), antibiotic combination therapy(OR=1.951; 95% CI 1.020～3.732), and nerve damage (OR=3.013; 95% CI 1.278～7.101). Multivariable analysis showed that ICU stay >7 days (OR=1.867; 95% CI 1.609～20.026), beta-lactamase inhibitor antibiotics (OR=7.750; 95% CI 2.219～27.071), and carbapenem (OR=9.143; 95% CI 2.259～37.01)are independent risk factors for VAP carbapenem caused by Carbapenem-resistant Enterobacteriaceae. A high resistance rate of CRE isolated from VAP indicated that the infected patients featured higher mortality and longer hospital stay time than the control group. Multiple risk factors for CRE infection and their control can effectively prevent the spread of VAP.